Regulation of short-chain fatty acids in the immune system - Liu, Xiao-feng; Shao, Jia-hao; Liao, Yi-Tao; Wang, Li-Ning; Jia, Yuan; Dong, Peng-jun; Liu, Zhi-zhong; He, Dan-dan; Li, Chao; Zhang, Xian (Frontiers in Immunology, 2023)
A growing body of research suggests that short-chain fatty acids (SCFAs), metabolites produced by intestinal symbiotic bacteria that ferment dietary fibres (DFs), play a crucial role in affecting the health status of symbiotes. SCFAs act on a variety of cell types to regulate a variety of important biological processes, including host metabolism, intestinal function, and the immune system. SCFAs also affect the function and fate of immune cells. This finding comprises a new concept in immune metabolism and provides a better understanding of the regulatory role of SCFAs in the immune system, which plays a key role in preventing and treating disease. The mechanism through which SCFAs respond to the immune response and immune tolerance has become increasingly clear. This review summarizes the different mechanisms through which SCFAs act in cells. According to the latest research status, the regulatory role of SCFAs in the innate immune system, including NLRP3 inflammasomes, receptors of TLR family members, neutrophils, macrophages, natural killer cells, eosinophils, basophils and innate lymphocyte subsets, is emphasized. The regulatory role of SCFAs in the adaptive immune system, including T-cell subsets, B cells, and plasma cells, is also highlighted. In addition, we discuss the role that SCFAs play in regulating allergic airway inflammation, colitis, and osteoporosis by influencing the immune system. these findings provide evidence for determining treatment options through metabolic regulation.